Bloom Filter-Based Advanced Traceback Scheme in Wireless Sensor Networks - Seoksoo Kim; Jong Hyun Kim; Sungmo Jung (Sensors, 2012)
Many recent studies have focused on traceback schemes with the aim of finding the source of spoofed malicious packets and tracing the path of denial-of-service attacks. Although such schemes are academically well known, most exhibit some critical points in wireless sensor networks, which could become a significant issue as they are increasingly used for IP networks. This paper suggests an advanced traceback scheme based on existing Bloom filter methods. The proposed traceback scheme extends the basic Bloom filter design, enabling it to identify which entity added a given element, albeit with the incursion of false positives. However, our scheme allows only specific tracebacks, which can reduce the false positive rate of a node near a sink. Performance results show that the scheme can perform efficient tracebacks with very few false positives.